Pollen tube competition as a mechanism of prezygotic reproductive isolation between Mimulus nasutus and its presumed progenitor M. guttatus - Diaz, A (The New phytologist, 1999)
This paper considers the extent to which differences in pollen tube growth rates can provide prezygotic reproductive isolation between Mimulus nasutus and its presumed progenitor, Mimulus guttatus. Mimulus nasutus is partially cleistogamous, but its larger chasmogamous flowers offer appreciable opportunity for outcrossing. Mimulus nasutus was found to have smaller pollen grains and shorter styles than M. guttatus. No differences were observed in pollen grain germination on conspecific and heterospecific stigmas. However, pollen tube growth rates of M. nasutus were found to be much slower than those of M. guttatus in the styles of that species. Consequently, any M. nasutus pollen transferred to an M. guttatus stigma was found to be competitively disadvantaged in an M. gutattus style. By contrast, no difference in pollen tube growth rate was detected between the species when growing in M. nasutus styles, possibly because M. nasutus styles are unable to support fast pollen tube growth. We tested the prediction from the pollen tube studies that a 50∶50 mix of M. guttatus and M. nasutus pollen would produce 50% hybrid seeds when M. nasutus was the maternal parent, and near to 0% hybrid seed when M. guttatus was the maternal parent. The results were found to support this prediction. We conclude that pollen-pistil interactions can effect strong reproductive isolation between these species, as M. guttatus pollen tubes have a competitive advantage over those of M. nasutus in an M. guttatus style, but not in an M. nasutus style